ANALYSIS OF CRITICAL THINKING IN CLASS 4 STUDENTS OF SDN 2 KUTOSARI IN THEMATIC LEARNING 2013 CURRICULUM - Marchelina Dwi Saputri; Kartika Chrysti Suryandari (Universitas Sebelas Maret, 2018)
Thematic learning in 2013 curriculum has competence time front that is ability thinking clear and critical. Student could said have ability critical thinking if they pass by 6 steps of Critical thinking. So this study was a purpose was to analyze critical thinking in class 4 students of SD N 2 Kutosari in thematic learning 2013 curriculum. This study used descriptive qualitative method. The research subjects were the fourth grade studenst of SD N 2 Kutosari. Data collection though observation, documentation and interview to the fourth grade student. Result research show ability critical thinking of class 4 student of SDN 2 Kutosari already exists, but students do not always think critically but only in limited learning. conducted students begin to be critical with 47,72% of students able to think critically. So the teacher lures students to think critically based on six step of critical thinking